Counseling Practice towards Folic Acid use among Health Care Provider's in Selected Public Hospitals in Addis Ababa, Ethiopia - Fetlework Aneteneh; Endalew Gemechu Sendo; Tigistu Gebretensaye (Mashhad University of Medical Sciences, 2021)
Background: Periconceptional folic acid supplementation is an effective way to prevent neural tube defects (NTDs) and other congenital anomalies. It is shown that 9.7% of healthcare providers practiced periconceptional folic acid supplements in Ethiopia. Fewer than 50% of women receive information on folic acid before or only during pregnancy. This study was conducted to assess folic acid supplementation counseling practices among health care providers. Methods: This institution-based cross-sectional study was conducted on 421 healthcare providers in selected public hospitals, Addis Ababa, Ethiopia. The hospitals were selected using a lottery sampling method, and a systematic random method was used to enroll participants. A structured self-administered instrument was used to gather information from participants. Data were checked for completeness and entered into Epi-Data software (version 3.1) and exported to SPSS software (version 25) for analysis. Descriptive statistics were used to describe participants' characteristics, and logistic regression, such as bivariate and multivariable analysis, were tested for associations. The level of significance was determined at a p-value of Results: In this study,periconceptional folic acid supplementation counseling practice wasfound in 51% of participants. Profession,salary, work load, patient flow, and assisted birth of a neonate with NTD were the factors associated with counseling practice (adjusted odds ratio [AOR]=3.215, 95% CI:1.085-9.523,  AOR=0.213, 95% CI:0.95-0.487, AOR= 0.427 95% CI:0.213-0.859, AOR=0.223, 95% CI: 0.1-0.498, and AOR=15.107 95% CI:8.157-27.979, respectively). Conclusion: Health care providers demonstrated a good level of knowledge and counseling practice about the folic acid supplement in this study. Medical doctor, salary, workload, patient flow, assisted birth of a neonate with NTD were found predictors for counseling practice.